Análise da influência dos geradores de vórtices por meio do estudo de suas posições em turbinas eólicas de pequeno porte - Lopes, Luann Marcos Gondim (Universidade Federal Rural do Semi-Árido, 2018)
From the need to identify mechanisms capable of improving the efficiency of small wind turbines, the present study aims to analyze the influence of devices known as vortex generators that have the function of generate flow disturbances, however, in a controlled way and known. The survey was of bibliographic and experimental/mathematical type. For your accomplishment, if performed simulations of three profiles that make up the projected blade used, without the use of vortex generators and generators to 25% and 50% of the chord. Still considered situations with and without twist in the profile, in incompressibility condition and the wind velocity of 3 m/s, and calculated a relative velocity in order to adapt the simplifications used. As a result, it was noted the influence caused by the devices cited in the run-off, as the increase in the kinetic energy in the region closest to the upper surface of the profile, in addition to the increase in drag force and fall in lift force, deflection and rotation. Thus, one could say that the vortex generators influence directly in the flow, being, for profiles analyzed, causing the fall of equipment efficiency, making it inappropriate for the situations mentioned.
Monografia
Keywords: Geradores de vórtices; Turbinas eólicas; CFD; Escoamento turbulento.; ENGENHARIAS::ENGENHARIA MECANICA